Metabotropic Glutamate 2/3 Receptors and Epigenetic Modifications in Psychotic Disorders: A Review - Matrisciano, Francesco (Curr Neuropharmacol, 2016)
Schizophrenia and Bipolar Disorder are chronic psychiatric disorders, both considered as “major psychosis”; they are thought to share some pathogenetic factors involving a dysfunctional gene x environment interaction. Alterations in the glutamatergic transmission have been suggested to be involved in the pathogenesis of psychosis. Our group developed an epigenetic model of schizophrenia originated by Prenatal Restraint Stress (PRS) paradigm in mice. PRS mice developed some behavioral alterations observed in schizophrenic patients and classic animal models of schizophrenia, i.e. deficits in social interaction, locomotor activity and prepulse inhibition. They also showed specific changes in promoter DNA methylation activity of genes related to schizophrenia such as reelin, BDNF and GAD67, and altered expression and function of mGlu2/3 receptors in the frontal cortex. Interestingly, behavioral and molecular alterations were reversed by treatment with mGlu2/3 agonists. Based on these findings, we speculate that pharmacological modulation of these receptors could have a great impact on early phase treatment of psychosis together with the possibility to modulate specific epigenetic key protein involved in the development of psychosis. In this review, we will discuss in more details the specific features of the PRS mice as a suitable epigenetic model for major psychosis. We will then focus on key proteins of chromatin remodeling machinery as potential target for new pharmacological treatment through the activation of metabotropic glutamate receptors.